THE EFFECTIVENESS OF MOMEDU CARE ON PREGNANCY-RELATED ANXIETY AMONG THIRD-TRIMESTER PREGNANT WOMEN - Maesaroh Maesaroh; Ade Rahayu Prihartini; Siti Juariah (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
Pregnancy-related anxiety is a common psychological problem experienced by women during the third trimester of pregnancy. Anxiety before childbirth may affect maternal emotional well-being and pregnancy outcomes. Digital antenatal education has recently become a potential approach to support maternal mental health through accessible and flexible health information. This study aimed to determine the effectiveness of MomEdu Care in reducing pregnancy-related anxiety among third-trimester pregnant women at Puskesmas Pulomerak. This study used a pre-experimental design with a one-group pretest-posttest approach. A total of 30 third-trimester pregnant women were recruited using purposive sampling. Anxiety levels were measured using the Pregnancy-Related Anxiety Questionnaire-Revised 2 (PRAQ-R2) before and after the intervention. Respondents used the MomEdu Care platform independently for two weeks. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed that the mean anxiety score decreased from 36.63 ± 1.97 before the intervention to 29.20 ± 1.67 after the intervention. Statistical analysis showed a significant difference between pretest and posttest scores (p-value = 0.000; p < 0.05). MomEdu Care was effective in reducing pregnancy-related anxiety among third-trimester pregnant women and may serve as an accessible digital antenatal education medium in primary healthcare settings.